Monitoring/characterization of stickies contaminants coming from a papermaking plant – Toward an innovative exploitation of the screen rejects to levulinic acid. (March 2016) - Licursi, Domenico; Antonetti, Claudia; Martinelli, Marco; Ribechini, Erika; Zanaboni, Marco; Raspolli Galletti, Anna Maria
Graphical abstract: Highlights: Streams coming from mechanical screening systems of a papermaking plant were analyzed. Analytical pyrolysis of output rejected stream evidenced EVA and SBR copolymers. Screen rejects contain also a residual cellulose fraction. Hydrothermal conversion to levulinic acid was studied. Abstract: Recycled paper needs a lot of mechanical/chemical treatments for its re-use in the papermaking process. Some of these ones produce considerable rejected waste fractions, such as " screen rejects ", which include both cellulose fibers and non-fibrous organic contaminants, or " stickies", these last representing a shortcoming both for the papermaking process and for the quality of the final product. Instead, the accepted fractions coming from these unit operations become progressively poorer in contaminants and richer in cellulose. Here, input and output streams coming from mechanical screening systems of a papermaking plant using recycled paper for cardboard production were sampled and analyzed directly and after solvent extraction, thus confirming the abundant presence of styrene-butadiene rubber (SBR) and ethylene vinyl acetate (EVA) copolymers in the output rejected stream and cellulose in the output accepted one. Despite some significant drawbacks, the " screen reject " fraction could be traditionally used as fuel for energy recovery within the paper mill, in agreement with the integrated recycled paper mill approach. The waste, which still contains a cellulose fraction, can be also exploited by means of the hydrothermal route to give levulinic acid, a platform chemical of very high value added.